2013
DOI: 10.1515/dmdi-2013-0050
|View full text |Cite
|
Sign up to set email alerts
|

Caffeic acid inhibits organic anion transporters OAT1 and OAT3 in rat kidney

Abstract: These findings show that caffeic acid inhibits OAT1 and OAT3 in the rat kidney.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…Here, the active secretion of 6-CF was inhibited by probenecid and d -malate, suggesting that it was mediated by renal rOat1 and rOat3. Phenolsulfonphthalein is often used to investigate renal organic anion transport in vivo . ,,, For example, we previously examined the effects of lithium on the renal organic anion transport using phenolsulfonphthalein . Sakurai et al used phenolsulfonphthalein for cellular study, but the determination of phenolsulfonphthalein by an absorption spectrometer showed a lower limit of detection of several μM.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Here, the active secretion of 6-CF was inhibited by probenecid and d -malate, suggesting that it was mediated by renal rOat1 and rOat3. Phenolsulfonphthalein is often used to investigate renal organic anion transport in vivo . ,,, For example, we previously examined the effects of lithium on the renal organic anion transport using phenolsulfonphthalein . Sakurai et al used phenolsulfonphthalein for cellular study, but the determination of phenolsulfonphthalein by an absorption spectrometer showed a lower limit of detection of several μM.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the renal handling of the flavonoid and its effect on renal transporters is an important issue from the standpoint of nutritional research. For OAT1 and OAT3, interactions with various dietary components, such as flavonoids and their conjugates, phenolic acids, and phenylpropanoids, are demonstrated by the inhibition of OAT-mediated transport of model substrates. We previously investigated the effects of natural compounds on OAT1 and OAT3 function using human OAT1- and OAT3-expressing cells and the fluorescent organic anion 6-carboxyfluorescein (6-CF) and found that several phenylpropanoids inhibit OAT1 and OAT3 functions …”
Section: Introductionmentioning
confidence: 99%
“…It has also been reported that caffeic acid inhibits organic anion transporters (OAT1 and OAT3) in rat kidneys. [42] However, there has been no report on the relationship between caffeic acid and organic cation transporter (OCT), and OCTs have a close relationship with the entry of CDDP into kidney cells [43]. Phenylacetylglycine may be a suitable biomarker associated with mitochondrial toxicity [44].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that caffeic acid from coffee, fruits, and vegetables significantly inhibits OAT3 (IC 50 = 5.4 μM) [ 71 ]. Yuichi et al uncovered that caffeic acid inhibits substrate uptake by OAT3 in a concentration-dependent manner (IC 50 < 10 μM) ( Table 3 ) [ 80 ].…”
Section: Natural Bioactive Inhibitors Of Oat3mentioning
confidence: 99%